Plasmodium APC3 mediates chromosome condensation and cytokinesis during atypical mitosis in male gametogenesis - Wall, Richard J.; Ferguson, David J. P.; Freville, Aline; Franke-Fayard, Blandine; Brady, Declan; Zeeshan, Mohammad; Bottrill, Andrew R.; Wheatley, Sally; Fry, Andrew M.; Janse, Chris J.; Yamano, Hiroyuki; Holder, Anthony A.; et al. (Nature Publishing Group, 2018)
The anaphase promoting complex/cyclosome (APC/C) is a highly conserved multi-subunit E3 ubiquitin ligase that controls mitotic division in eukaryotic cells by tagging cell cycle regulators for proteolysis. APC3 is a key component that contributes to APC/C function. Plasmodium, the causative agent of malaria, undergoes atypical mitotic division during its life cycle. Only a small subset of APC/C components has been identified in Plasmodium and their involvement in atypical cell division is not well understood. Here, using reverse genetics we examined the localisation and function of APC3 in Plasmodium berghei. APC3 was observed as a single focus that co-localised with the centriolar plaque during asexual cell division in schizonts, whereas it appeared as multiple foci in male gametocytes. Functional studies using gene disruption and conditional knockdown revealed essential roles of APC3 during these mitotic stages with loss resulting in a lack of chromosome condensation, abnormal cytokinesis and absence of microgamete formation. Overall, our data suggest that Plasmodium utilises unique cell cycle machinery to coordinate various processes during ndomitosis, and this warrants further investigation in future studies.